HUKUM ISLAM DAN BUDAYA (Studi Akumulasi ‘Urf dalam Fatwa Dewan Syariah Nasional (DSN) Tentang Produk Perbankan Syariah di Indonesia) - Machrus, Ali (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2021)
'Urf as one of ijtihad method in ushul fiqih, synergize social reality of Indonesian society and sunnah of Rasulullah SAW. By digging and raising local wisdom of Indonesian people in economy without leaving the boundaries of sharia with the aim to promote and develop the application of Islamic principles, sharia and traditions in financial transactions, banking and other business related. The aims of this paper are: 1) To explain the reasons of the Fatwa of the National Sharia Board (DSN) on sharia banking products based on its consideration 'urf, and 2) To analyze the' urf position in the fatwa of National Sharia Board (DSN) on banking products Sharia when viewed from the side of the development of Islamic banking products in Indonesia. The results of analysis in this paper that: 1) Determination of fatwa-fatwa National Sharia Board (DSN) on Islamic banking products, namely: demand deposits, savings, and deposits made on the basis of consideration 'urf. Due to the fact of history and has been known by many people in Indonesia in transactions with banking 2) The position of urf in the fatwa of the National Sharia Council (DSN) on sharia banking products in terms of development of Islamic banking products in Indonesia as a general consideration when the approach nash qath'i and qauli approach can not be done.